2010
DOI: 10.1007/s00404-010-1405-5
|View full text |Cite
|
Sign up to set email alerts
|

Cervical polyps: evaluation of routine removal and need for accompanying D&C

Abstract: Routine removal of cervical polyps, although not mandatory, seems clinically prudent because pathological evaluation is needed to confirm the diagnosis and to rule out other possibilities. 10.9% of postmenopausal patients and 7.8% of premenopausal patients were diagnosed with any endometrial pathology accompanying cervical polyp. Therefore, cervical polyps can be a sign of endometrial disease, especially in postmenopausal women with cervical polyp endometrium should be evaluated more carefully.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 9 publications
0
12
1
Order By: Relevance
“…A previous study observed that pathological changes in patients with cervical polyps are frequently endometrial in origin [4]. Few studies recommend endometrial sampling in addition to polypectomy irrespective of their symptoms [9][10][11]. However, according to other studies, polypectomy in cases with asymptomatic polyps was not costeffective and should be recommended only for symptomatic cases [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study observed that pathological changes in patients with cervical polyps are frequently endometrial in origin [4]. Few studies recommend endometrial sampling in addition to polypectomy irrespective of their symptoms [9][10][11]. However, according to other studies, polypectomy in cases with asymptomatic polyps was not costeffective and should be recommended only for symptomatic cases [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Cervical polyps are considered to be focal hyperplastic protrusions of endocervical folds rather than true neoplasms. 24 Most patients present during the perimenopausal period in the fifth decade of life. Patients may present with menorrhagia, postmenopausal bleeding, and vaginal discharge.…”
Section: Cervical Massesmentioning
confidence: 99%
“…Approximately 0.1% of cervical polyps are associated with malignancy, and approximately 10% of patients with cervical polyps also have coexisting endometrial disorders (eg, hyperplasia, polyp, and carcinoma). 24 Cervical cancer is the third most common cancer in women worldwide and is most common in developing countries. Risk factors for cervical cancer include infections with high-risk human papillomavirus (types 16 and 18), oral contraceptive pills, low socioeconomic status, smoking, multiple sexual partners, human immunodeficiency virus infection, and other sexually transmitted diseases.…”
Section: Cervical Massesmentioning
confidence: 99%
“…Patients may also present with abnormal vaginal bleeding. The prevalence of malignancy and dysplasia is relatively uncommon (0.1% and 0.4%, respectively) . Pathological evaluation is needed to confirm and/or rule out other diagnoses.…”
Section: Cervixmentioning
confidence: 99%